A method for preparing a silver film layer on a molybdenum foil surface
By plating the titanium layer and silver layer at high temperature on the surface of the molybdenum foil, and using ion sources to enhance Ar+ bombardment and high-temperature annealing, the problem of silver plating on the surface of the molybdenum foil is solved, and the weldability and conductivity of the material are significantly improved, meeting the performance requirements of aerospace level.
Patent Information
- Application Number
- CN202411644812.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art has problems of poor adhesion and poor coating quality when electroplating silver on the surface of molybdenum foil, and it is difficult to form a solid solution between molybdenum and silver, which affects welding and conductivity.
The method of preparing a silver film layer on the surface of molybdenum foil is used to plating the titanium layer and the silver plating layer at high temperature, and the Ar+ bombardment is added through an ion source, combined with two high-temperature annealings to enhance the interfacial metallurgical bonding and crystallinity.
The bonding force between the silver film layer and the titanium film layer is significantly improved, the weldability and conductivity of the Mo-Ti-Ag layered metal-based composite material is enhanced, the temperature impact requirements of the aerospace level are met, and the life of the material is extended.
Smart Images

Figure CN119753569A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of composite materials, and in particular to a method for preparing a silver film layer on the surface of a molybdenum foil. Background Art
[0002] Molybdenum and molybdenum alloys are high-temperature resistant materials that can maintain high strength at high temperatures. At the same time, it also has high thermal conductivity and low thermal expansion coefficient, and good heat shock resistance. The material also has good electrical conductivity and wear resistance. Due to the above advantages, molybdenum and molybdenum alloys are widely used in the aerospace field, including molybdenum foil for interconnection sheets of solar arrays of spacecraft satellites, spacecraft and space stations. However, molybdenum has relatively poor weldability and will oxidize strongly at high temperatures, and this oxide film has no protective effect. For the interconnection sheet material of spacecraft solar panels, good weldability and electrical conductivity are indispensable, and silver has good brazing performance and electrical conductivity. To solve this problem, molybdenum and silver can be layered to prepare molybdenum / silver layered metal matrix composite materials, but it is difficult to form an alloy solid solution between molybdenum and silver. The solubility of molybdenum in silver is very small. At 1600℃, the solubility of molybdenum in silver is only about 5%. Therefore, it is difficult to electroplate silver on the surface of molybdenum. Direct silver plating often does not adhere firmly and the coating quality is poor.
[0003] The existing ion source is generally used in magnetron sputtering deposition technology. In the process of depositing the metal intermediate layer by magnetron sputtering technology, the purity of the metal target material with good solid solubility in molybdenum is required to be above 99.9%, and the purity of the protective gas including inert gas is required to be above 99.9%. In addition, the metal intermediate layer should not be too thick, otherwise it will easily make the interface brittle, which will reduce the interface bonding strength between the molybdenum substrate and the silver layer. It also has strict requirements on the process conditions such as working gas pressure, temperature, time, and power. This will lead to high material selection requirements and high cost in the preparation process, and the scope of implementation options is very narrow.
[0004] At present, the industry generally adopts the method of pre-plating and impact strength to solve the problem of difficult molybdenum electroplating, that is, a very thin metal layer (such as chromium, nickel, gold, rhodium, platinum, etc.) that can form an alloy with molybdenum is first electroplated on the surface of molybdenum, and then silver is electroplated after high-temperature heat treatment. Since the preparation of metal-based composite materials often requires multiple high-temperature annealing, and may involve hydrogen protection annealing, and some metals are sensitive to hydrogen, such as palladium metal, which absorbs more hydrogen during the preparation process, and the volume will significantly expand and become brittle or even break into fragments. Moreover, the electroplated silver layer has its own defects. Usually, the electroplated coating has a columnar crystal structure, poor density, poor alloy bonding, and vacancies and defects inside. In the low-Earth orbit environment, atomic oxygen can enter the interior through these defects of the coating material and corrode it. Such long-term slow atomic oxygen erosion can still cause serious damage to the performance of the interconnect.
[0005] In the prior art Chinese application CN106048534A, the intermediate layer is plated with a nickel-chromium alloy, and the thickness of the evaporated layer is 300-500 nm. Summary of the invention
[0006] Based on the above problems, the present invention proposes a method for preparing a silver film layer on the surface of a molybdenum foil, wherein when the titanium layer and the silver layer are plated, an ion source is used to increase the Ar + Bombardment can greatly increase the interface metallurgical bonding, crystallinity, and tensile strength. When the titanium coating reaches about 600nm, it can still maintain a high degree of bonding between the silver layer and the titanium layer and reach aviation level. It has excellent use effect and long service life, overcoming the shortcomings and defects mentioned in the background technology.
[0007] To achieve the above objectives, this application adopts the following technical solutions:
[0008] The invention of this application is to provide a method for preparing a silver film layer on the surface of a molybdenum foil, the steps are:
[0009] 1) placing the pretreated molybdenum foil substrate under vacuum conditions and performing ion source bombardment cleaning;
[0010] 2) Titanium coating: The molybdenum foil substrate is heated at high temperature under vacuum conditions, and a titanium film is first evaporated using an electron gun, and an ion source is turned on to assist in the titanium coating, increasing the Ar + Bombard the titanium film layer, rotate the molybdenum foil substrate, evaporate the titanium film layer on the first side of the molybdenum foil substrate, and stop when the thickness of the titanium film layer is reached. After the evaporation of the first titanium film layer is completed, then evaporate the titanium film layer on the second side of the molybdenum foil substrate. The process is the same as that of evaporating the first titanium film layer. After the evaporation is completed, turn off the ion source and perform the first annealing treatment;
[0011] 3) Silver-plated film layer: The process of evaporating the silver film layer is the same as that of evaporating the titanium film layer in step 2). After the evaporation is completed, the ion source is turned off and a second annealing treatment is performed;
[0012] 4) Packaging: The molybdenum foil after step 3) is cooled to room temperature and packaged with nitrogen.
[0013] Furthermore, in step 2), the titanium-plated film layer has a thickness of 15 nm to 600 nm, preferably 100 nm to 600 nm.
[0014] Furthermore, the high temperature of the molybdenum foil substrate described in step 2) is heated to 300-500°C.
[0015] Furthermore, the power parameters of the electron gun are adjusted to: high voltage: 6-10KW, beam current: 0.05-0.3A, filament voltage: 50-70V, filament current: 1-2A, evaporation rate: 1.5-3nm / s.
[0016] Furthermore, the parameters of the ion source are adjusted to: acceleration current of 5-15 mA, ion beam current of 80-100 mA, plate voltage of 340-360 V, anode current of 2-5 A, and cathode filament current of 14-17 A.
[0017] Furthermore, the evaporated silver film layer has an evaporation thickness of 3 to 7 μm.
[0018] Furthermore, the evaporation time of the silver film layer is 20 to 50 minutes.
[0019] Furthermore, after the first titanium film layer is evaporated in step 2), the molybdenum foil substrate is turned 180° to the back side, and then the second titanium film layer is evaporated on the molybdenum foil substrate.
[0020] Furthermore, the temperature of the first annealing is 700-900°C, and the temperature of the second annealing is 650-900°C.
[0021] Furthermore, the time for the first annealing and the second annealing is 10 to 30 minutes.
[0022] Compared with the prior art, this application has the following advantages:
[0023] (1) The present invention forms a metallurgical bond at the metal interface by plating a titanium film layer and a silver film layer at a high temperature (usually above 300 degrees), using an ion source to increase Ar+ bombardment, and performing two high-temperature annealings. The interface bonding is very good and there is no cracking due to temperature differences and different expansion coefficients. The interconnector prepared from the Mo-Ti-Ag layered metal matrix composite material can meet the temperature shock requirements of the outer space.
[0024] (2) After single-point resistance spot welding of the prepared Mo-Ti-Ag layered metal matrix composite material and the solar GaAs cell of the spacecraft, its maximum welding tensile (interface) strength reached 480 gf and the average strength reached 420 gf. This strength index exceeds the national military standards and the index requirements put forward by aerospace users. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of Mo-Ti-Ag layers.
[0026] Figure 2 SEM image of the cross-section morphology of Mo-Ti-Ag layer.
[0027] Figure 3 SEM image of the surface morphology of Mo-Ti-Ag layer.
[0028] Figure 4 XRD pattern of Mo-Ti-Ag layer.
[0029] Figure 5 Tensile test curve of the interface bonding strength of Mo-Ti-Ag layered composite materials. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below. However, it should be understood that the description here is only used to explain the present application and is not used to limit the scope of the present application.
[0031] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present application, and the terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The reagents and instruments used herein are all commercially available, and the characterization means involved can refer to the relevant descriptions in the prior art, which will not be repeated herein.
[0032] In order to further understand the present application, the present application is further described in detail below in conjunction with the best embodiment.
[0033] Example 1
[0034] The present invention provides a method for preparing a silver film layer on the surface of a molybdenum foil, the steps of which are:
[0035] 1) placing the pretreated molybdenum foil substrate under vacuum conditions and performing ion source bombardment cleaning;
[0036] The pretreatment includes first removing the surface oil stains on the molybdenum foil with an alkaline degreasing agent, washing with deionized water, then etching with acid to remove the surface oxide film, washing with deionized water, and finally ultrasonically cleaning with anhydrous ethanol;
[0037] The vacuum condition is to evacuate to less than 6×10 -3 Pa;
[0038] The ion source bombards and cleans the surface of the molybdenum foil substrate, heats the molybdenum foil substrate, and bakes and degasses it.
[0039] 2) Titanium coating: The molybdenum foil substrate is heated at high temperature under vacuum conditions, and a titanium film is first evaporated using an electron gun, and an ion source is turned on to assist in the titanium coating, increasing the Ar +Bombard the titanium film layer, place the molybdenum foil substrate horizontally, rotate in the horizontal direction at a speed of 20 rpm, evaporate the titanium film layer on the first side of the molybdenum foil substrate, and stop when the thickness of the titanium film layer is reached. After the evaporation of the first titanium film layer is completed, turn the molybdenum foil substrate 180° to the back, and then evaporate the second titanium film layer of the molybdenum foil substrate. The process is the same as that of evaporating the first titanium film layer. After the evaporation is completed, turn off the ion source and perform the first annealing treatment to make the coating layer react to generate molybdenum-titanium intermetallic compounds to obtain a coating layer with uniform distribution and strong bonding strength.
[0040] 3) Silver coating: The annealed molybdenum foil substrate is silver-coated under the same vacuum conditions using the same titanium coating process. The molybdenum foil substrate is placed horizontally and rotated in the horizontal direction at a speed of 20 rpm. The first silver film layer of the molybdenum foil substrate is evaporated and stopped when the thickness of the silver coating layer is reached. During the silver coating, the molybdenum foil substrate is heated at a high temperature, and an ion source is turned on to assist the silver coating layer. The Ar + After bombarding the silver film layer and evaporating the first silver film layer, the molybdenum foil substrate is flipped 180° to the back side, and then the second silver film layer of the molybdenum foil substrate is evaporated. The process is the same as that of evaporating the first silver film layer. After the evaporation is completed, the ion source is turned off and a second annealing treatment is performed to allow the titanium film layer and the silver film layer to fully react to generate silver-titanium intermetallic compounds, thereby obtaining a uniformly distributed and strongly bonded coating layer.
[0041] 4) Packaging: The molybdenum foil after step 3) is cooled to room temperature and packaged with nitrogen.
[0042] As a further preferred embodiment, the titanium-plated film layer has a thickness of 15 nm to 600 nm, preferably 100 nm to 600 nm, for example, 15 nm, 20 nm, 30 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm or any value between any two values. In the prior art, the effect achieved by the titanium-plated film layer having a thickness of any value between 5 and 100 nm is close to the effect achieved by the titanium-plated film layer having a thickness of any value between 5 and 100 nm in the present invention, so the present application does not provide specific embodiments.
[0043] As a further preferred embodiment, in step 2), the molybdenum foil substrate is heated to 300-500°C during coating, for example, 300°C, 350°C, 400°C, 450°C, 500°C or any value between any two values.
[0044] As a further preferred implementation manner, the electron gun power parameters are adjusted to: high voltage: 6-10KW, beam current: 0.05-0.3A, filament voltage: 50-70V, filament current: 1-2A, evaporation rate: 1.5-3nm / s. Although the coating can be completed by adjusting these parameters to a certain extent or a small extent, it is found through experiments that, however, under the above-mentioned parameter state, the electron gun titanium coating effect is the best. This parameter can better promote the combination and penetration of the molybdenum / titanium layer, so the above parameters are preferred.
[0045] As a further preferred embodiment, the ion source parameters are adjusted to: acceleration current of 5-15 mA, ion beam current of 80-100 mA, screen voltage of 340-360 V, anode current of 2-5 A, cathode filament current of 14-17 A, so that the internal stress of titanium atoms is released in a short time, titanium pinholes are reduced, the film layer is more uniform, and the film layer quality is better.
[0046] As a further preferred embodiment, the evaporated silver film layer has an evaporation thickness of 3 to 7 μm, for example, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or any value between any two values.
[0047] Furthermore, the evaporation time of the evaporated silver film layer is 20 to 50 minutes, for example, it can be 20 minutes, 30 minutes, 40 minutes, 50 minutes or any value between any two values.
[0048] As a further preferred embodiment, the temperature of the first annealing is 700-900°C, for example, it can be 700°C, 720°C, 750°C, 800°C, 850°C, 900°C or any value between any two values. The temperature of the second annealing is 650-750°C, for example, it can be 650°C, 680°C, 700°C, 720°C, 750°C or any value between any two values.
[0049] As a further preferred embodiment, the time for the first annealing and the second annealing is 10 to 30 minutes, for example, 10 min, 15 min, 20 min, 25 min, 30 min or any value between any two values.
[0050] During evaporation, the distance between the evaporation source and the substrate is set to 45 cm. Before evaporation, the molybdenum foil substrate is heated to 150 ° C for baking and degassing to remove the residual organic matter on the surface. -2After the Pa level, argon gas is introduced, and argon plasma is formed in the vacuum chamber through the Kaufman ion source, and the substrate surface is bombarded and cleaned for more than 15 minutes to remove the oxide layer or other impurities on the substrate surface. Among them, the relevant parameters of the Kaufman ion source are: the acceleration current is 10mA, the ion beam current is 80mA, the electron beam current is about 1.2 times the ion beam current, and the plate voltage is 350V.
[0051] The obtained molybdenum foil substrate-titanium intermediate layer-silver layer composite structure is annealed. During the annealing process, high temperature can increase the atomic activity, promote the mutual diffusion of atoms at the interface of molybdenum / titanium intermediate layer and titanium intermediate layer / silver, realize alloying at the interface, and further improve the interface bonding strength of Mo and Ag.
[0052] Since the present invention uses an ion source to increase Ar+ bombardment at high temperature (usually above 300 degrees) and performs two high-temperature annealings at the same time by plating a titanium film layer and a silver film layer, the present invention does not require the purity of the metal target material having good solid solubility with molybdenum and the purity of the protective gas including the inert gas such as.
[0053] Example 2
[0054] In the present invention, the method for preparing a silver film layer on the surface of a molybdenum foil can also be completed in one device at the same time, and the vacuum coating machine is configured as a vacuum coating chamber, in which an ion source, an electron gun, a high-temperature heating component and a sample flipping component are integrated; the electron gun and the ion source are arranged at the bottom of the coating chamber, the high-temperature heating component is arranged at the back of the sample platform of the coating chamber, and the sample flipping component is at the front of the sample platform.
[0055] The present invention completes the electron gun coating process and annealing treatment on the same device, realizes the preparation of the silver film layer on the surface of the molybdenum foil, eliminates the hidden danger of product defects in the discontinuous production process, and ensures the quality and performance of the alloy coating products; the equipment of the present invention has a compact structure and complete functions, and saves both materials and energy.
[0056] Example 3
[0057] According to the content of this application, the preparation method of Example 1 is specifically described, and the specific description is as follows:
[0058] Test Example 1
[0059] A specific implementation process for preparing a silver film layer on the surface of a molybdenum foil is:
[0060] 1) Pretreatment: First, use an alkaline degreasing agent to remove surface oil on the molybdenum foil, wash it with deionized water, then etch it with 20% H2SO4 for 60s to remove the surface oxide film, wash it with deionized water, and finally use anhydrous ethanol ultrasonic cleaning for 15 minutes.
[0061] 2) Vacuum treatment: Place the pretreated molybdenum foil into a vacuum chamber and evacuate to 1×10 -3 Pa, bombard and clean the surface of the molybdenum foil substrate with an ion source for 15 minutes, heat the temperature of the molybdenum foil substrate to 150°C, and bake and degas for 15 minutes.
[0062] 3) Titanium coating: Use an electron gun to evaporate the titanium film layer under vacuum conditions, and adjust the electron gun power parameters to: high voltage: 8KW, beam current: 0.1A, filament voltage: 60V, filament current: 1.4A, evaporation rate: 1.5nm / s, the molybdenum foil substrate is placed horizontally, rotated in the horizontal direction, and the speed is 20 rpm. The first titanium film layer of the molybdenum foil substrate is evaporated. The thickness of the evaporated titanium film layer is 500nm, and the evaporation time is 30 minutes. When plating the titanium film layer, the temperature of the molybdenum foil substrate is heated to 300°C, and the ion source is turned on to assist the titanium coating layer. The parameters are adjusted to: acceleration current is 10mA, ion beam current is 90mA, screen voltage is 350V, anode current: 3A, cathode filament current: 15A, screen voltage, increase Ar + Bombard the titanium film layer, and after the first titanium film layer is evaporated, the molybdenum foil substrate is turned 180° to the back, and then the second titanium film layer of the molybdenum foil substrate is evaporated. The process is the same as that of evaporating the first titanium film layer. After the evaporation is completed, the ion source is turned off.
[0063] 4) First annealing treatment: After the evaporation is completed, the temperature in the vacuum chamber is raised to 900° C. and annealing treatment is performed for 30 minutes to allow the film layer to react to generate molybdenum-titanium intermetallic compounds.
[0064] 5) Silver-plated film: The annealed molybdenum foil substrate is silver-plated under the same vacuum conditions using the same titanium-plated film process. The electron gun power parameters are adjusted to: high voltage: 8KW, beam current: 0.1A, filament voltage: 60V, filament current: 1.5A, evaporation rate: 3nm / s, the molybdenum foil substrate rotates horizontally at a speed of 20 rpm, and the first silver film layer of the molybdenum foil substrate is evaporated. The thickness of the evaporated silver film layer is 5μm, and the evaporation time is 30 minutes. When the silver film is plated, the substrate temperature is heated to 300°C, and the ion source is turned on to assist the silver-plated film layer. The parameters are adjusted to: acceleration current is 10mA, ion beam current is 90mA, screen voltage is 350V, anode current: 3A, cathode filament current: 15A, screen voltage, increase Ar + The silver film layer is bombarded, and after the first silver film layer is plated, it is flipped 180 degrees to the back side, and then the second silver film layer of the molybdenum foil substrate is evaporated. The process is the same as that of evaporating the first silver film layer. After the evaporation is completed, the ion source is turned off.
[0065] 6) Second annealing treatment: After the evaporation is completed, the temperature in the vacuum chamber is raised to 650°C and annealing treatment is performed for 30 minutes to allow the titanium film layer and the silver film layer to fully react to form a silver-titanium intermetallic compound, such as Figure 1 shown.
[0066] 7) Packaging: After annealing, cool the sample to room temperature and open the furnace to package it with nitrogen.
[0067] 8) Morphology of Mo-Ti-Ag layered composites
[0068] Through the layer section, surface morphology SEM image, and layer XRD image of the Mo-Ti-Ag layered composite material, it can be seen that layer 1 is an Ag film with a thickness of 5 microns; layer 2 is a Ti intermediate layer with a thickness of about 0.5 microns; and layer 3 is a Mo foil. Figure 2 , 3 4 shows that after annealing, good metallurgical bonding is formed at the interface of Ag / Ti and Ti / Mo. The interface of Ag / Ti and Ti / Mo is well bonded without cracks.
[0069] 9) Interface bonding strength test of Mo-Ti-Ag layered composite materials
[0070] The interfacial bonding strength of Mo-Ti-Ag layered composite materials was tested using the peeling test method in the national standard GB / T 5270-2005. The Mo-Ti-Ag layered composite material was made into a sample with a diameter of 15 mm, and the Ag and Mo sides of the sample were respectively adhered to the middle of two aluminum bars with a cross-section of 5 cm in length using FM1000 adhesive to form a tensile test specimen. The sample was subjected to a tensile test using an INSTRON-5567 universal material testing machine. The tensile test was carried out at room temperature with a tensile speed of 5 mm / min. The tensile strength test curve is shown in Figure 1. Figure 5 As shown in the figure, the maximum load is 3821N and the tensile strength is 47Mpa. The fracture occurred at the interface between the binder and the Ag film, while the Ag film did not fall off the Mo foil, indicating that the Ag film and the Mo foil interface achieved metallurgical bonding and had very excellent bonding strength, which was greater than the bonding strength of the binder and the silver film, 41MPa.
[0071] Test Example 2
[0072] A specific implementation process for preparing a silver film layer on the surface of a molybdenum foil is:
[0073] Step 1) and step 2) are the same as those in Experimental Example 1;
[0074] 3) Titanium coating: The evaporation process is the same as that in Experimental Example 1. The electron gun power parameters and the horizontal rotation speed of the molybdenum foil substrate are the same as those in Experimental Example 1. The titanium film layer on the first side and the titanium film layer on the second side of the molybdenum foil substrate are evaporated. The thickness of the evaporated titanium film layer is 100 nm. The evaporation time is 25 minutes. During the coating, the temperature of the molybdenum foil substrate is heated to 350°C. At the same time, the ion source is turned on with the same parameters as in Experimental Example 1. After the evaporation is completed, the ion source is turned off.
[0075] 4) First annealing treatment: After the evaporation is completed, the temperature in the vacuum chamber is raised to 900° C. and annealing treatment is performed for 10 minutes.
[0076] 5) Silver-plated film layer: The evaporation process is the same as that of Experimental Example 1. When the silver-plated film layer is formed, the substrate temperature is heated to 350°C.
[0077] 6) Second annealing treatment: After the evaporation is completed, the temperature in the vacuum chamber is raised to 700° C. and annealing treatment is performed for 10 minutes.
[0078] 7) Packaging: After annealing, cool the sample to room temperature and open the furnace to package it with nitrogen.
[0079] 8) Morphology of Mo-Ti-Ag layered composites
[0080] The test method is the same as that in Test Example 1, and the test results are similar to those in Test Example 1. Layer 1 is an Ag film with a thickness of 5 microns; layer 2 is a Ti intermediate layer with a thickness of about 0.1 microns; and layer 3 is a Mo foil. After annealing, the interface between Ag / Ti and Ti / Mo is well bonded, and no cracks appear. In addition, the Ag film has no columnar crystal features and presents a dense granular crystal structure. At the interface between Ag / Ti and Ti / Mo, it is shown that a good metallurgical bond is formed at the interface.
[0081] 9) Interface bonding strength test of Mo-Ti-Ag layered composite materials
[0082] The test method is the same as that in Test Example 1
[0083] The test results show that the maximum load is 3653N and the tensile strength is 44Mpa.
[0084] Test Example 3
[0085] A specific implementation process for preparing a silver film layer on the surface of a molybdenum foil is:
[0086] Step 1) and step 2) are the same as those in Experimental Example 1;
[0087] 3) Titanium coating: The evaporation process is the same as that in Experimental Example 1. The electron gun power parameters and the horizontal rotation speed of the molybdenum foil substrate are the same as those in Experimental Example 1. The first and second titanium film layers of the molybdenum foil substrate are evaporated. The thickness of the evaporated titanium film layer is 600 nm. The evaporation time is 40 minutes. During the coating, the temperature of the molybdenum foil substrate is heated to 500°C. At the same time, the ion source is turned on with the same parameters as in Experimental Example 1. After the evaporation is completed, the ion source is turned off.
[0088] Step 4) is the same as in Experimental Example 1, and the annealing time is 20 minutes.
[0089] 5) Silver-plated film layer: The evaporation process is the same as that of Experimental Example 1. When the silver-plated film layer is formed, the substrate temperature is heated to 450°C.
[0090] 6) Second annealing treatment: After the evaporation is completed, the temperature in the vacuum chamber is raised to 750° C. and annealing treatment is performed for 20 minutes.
[0091] 7) Packaging: After annealing, cool the sample to room temperature and open the furnace to package it with nitrogen.
[0092] 8) Morphology of Mo-Ti-Ag layered composites
[0093] The test method is the same as that in Test Example 1, and the test results are similar to those in Test Example 1. Layer 1 is an Ag film with a thickness of 5 microns; layer 2 is a Ti intermediate layer with a thickness of about 0.6 microns; and layer 3 is a Mo foil. After annealing, the interface between Ag / Ti and Ti / Mo is well bonded, and no cracks appear. In addition, the Ag film has no columnar crystal features and presents a dense granular crystal structure. At the interface between Ag / Ti and Ti / Mo, it is shown that a good metallurgical bond is formed at the interface.
[0094] 9) Interface bonding strength test of Mo-Ti-Ag layered composite materials
[0095] The test method is the same as that in Test Example 1
[0096] The test results show that the maximum load is 3790N and the tensile strength is 46Mpa.
[0097] Comparative Example 1 (Prior Art)
[0098] A specific implementation process for preparing a silver film layer on the surface of a molybdenum foil is:
[0099] 1) Mo foil pretreatment
[0100] After the molybdenum foil substrate is polished with sandpaper, it is immersed in a degreasing solution (a mixed solution of NaOH: Na2 CO3: Na2 SiO3 = 3:2:1) for degreasing. After degreasing, the surface of the molybdenum foil substrate is rinsed with a large amount of deionized water. Then, the molybdenum foil substrate is placed in a 10% H2SO4 solution for etching for 10 minutes, and then rinsed with deionized water, and then ultrasonically cleaned in deionized water for 20 minutes, and then taken out and dried for use.
[0101] 2) Magnetron sputtering deposition of Ti intermediate layer
[0102] The molybdenum foil substrate treated in step (1) was placed in a vacuum coating chamber. A metal Ti with a purity of 99.99% was used as the target material, and high-purity Ar was used as the working gas. The vacuum was pre-evacuated to 5×10 -3Pa, after 30 minutes of plasma cleaning, the Ti target pulse DC power supply was turned on to deposit a Ti intermediate layer on the surface of the molybdenum foil substrate. The Ti target sputtering power was 800W, the bias voltage was -70V, the working gas pressure was 0.1Pa, and the deposition time was 20min, and a Ti layer (hereinafter referred to as Mo / Ti composite material) was deposited on the surface of the Mo foil.
[0103] (3) Magnetron sputtering deposition of Ag film
[0104] The Mo / Ti composite material treated in step (2) is placed in a vacuum coating chamber. A metal Ag with a purity of 99.99% is used as the target material, and high-purity Ar is used as the working gas. The vacuum chamber is pre-evacuated to 5×10 -3 Pa, after plasma cleaning for 30 minutes, turn on the pulsed DC power supply to deposit Ag film on the surface of Ti layer. Ag target sputtering power is 800W, bias voltage is -70V, working gas pressure is 0.1Pa, and deposition time is 5 hours. After deposition, cool to room temperature in a vacuum environment, then release gas and open the cavity to take out of the furnace.
[0105] (4) Annealing
[0106] The composite material treated in step (3) is placed in a high-temperature tube furnace and annealed in an argon atmosphere with a purity of 99.999% and a pressure of one standard atmosphere. The temperature is raised from room temperature to 700°C at a heating rate of 5°C / min and kept at this temperature for 5 hours. The composite material is cooled to room temperature in the furnace to obtain a Mo-Ti-Ag layered composite material.
[0107] 5) Morphology of Mo-Ti-Ag layered composites
[0108] The test method is the same as that in Experimental Example 1. The test results show that layer 1 is an Ag film with a thickness of 5 microns; layer 2 is a Ti intermediate layer with a thickness of about 0.1 microns; and layer 3 is a Mo foil. The interface bonding between Ag / Ti and Ti / Mo is good. In addition, the Ag film has a columnar crystal particle structure. At the interface between Ag / Ti and Ti / Mo, it is shown that a good metallurgical bonding is formed at the interface.
[0109] 6) Interface bonding strength test of Mo-Ti-Ag layered composite materials
[0110] The test method is the same as that in Test Example 1
[0111] The test results show that the tensile strength is 43 MPa, and the bonding strength is greater than the bonding strength between the adhesive and the silver film, which is 41 MPa.
[0112] Comparative Example 2
[0113] A specific implementation process for preparing a silver film layer on the surface of a molybdenum foil is:
[0114] Step 1) and step 2) are the same as those in Experimental Example 1;
[0115] 3) Titanium coating: The evaporation process is the same as that in Experimental Example 1. The electron gun power parameters and the horizontal rotation speed of the molybdenum foil substrate are the same as those in Experimental Example 1. The thickness of the evaporated titanium film layer is 500 nm. The evaporation time is 30 minutes. During coating, the temperature of the molybdenum foil substrate is heated to 300°C, and the ion source is not turned on.
[0116] 4) Same as Test Example 1.
[0117] 5) Silver-plated film layer: The evaporation process was the same as that in Experimental Example 1, but the ion source was not turned on.
[0118] Step 6) and step 7) are the same as those in Experimental Example 1.
[0119] 8) Morphology of Mo-Ti-Ag layered composites
[0120] The test method is the same as that in Experimental Example 1. The test results show that layer 1 is an Ag film with a thickness of 5 microns; layer 2 is a Ti intermediate layer with a thickness of about 0.5 microns; and layer 3 is a Mo foil. The interface bonding between Ag / Ti and Ti / Mo is average. In addition, the Ag film has a columnar crystal characteristic crystal particle structure. Metallurgical bonding is formed at the interface between Ag / Ti and Ti / Mo.
[0121] 9) Interface bonding strength test of Mo-Ti-Ag layered composite materials
[0122] The test method is the same as that in Test Example 1. The test results show that the maximum load is 1556N and the tensile strength is 20Mpa. The bonding strength is less than the bonding strength of the adhesive and the silver film, which is 41MPa.
[0123] Comparative Example 3
[0124] A specific implementation process for preparing a silver film layer on the surface of a molybdenum foil is:
[0125] Step 1 and step 2 are the same as those in Experimental Example 1;
[0126] 3) Titanium coating: The evaporation process is the same as that in Experimental Example 1. The electron gun power parameters and the horizontal rotation speed of the molybdenum foil substrate are the same as those in Experimental Example 1. The thickness of the evaporated titanium film layer is 500 nm. The evaporation time is 30 minutes. During coating, the temperature of the molybdenum foil substrate is heated to 100°C and the ion source is turned on at the same time. The parameters are the same as those in Experimental Example 1.
[0127] 4) Same as Test Example 1.
[0128] 5) Silver-plated film layer: The evaporation process is the same as that of Experimental Example 1, and the temperature of the molybdenum foil substrate is heated to 100° C. during the coating process.
[0129] Step 6) and step 7) are the same as those in Experimental Example 1.
[0130] 8) Cross-sectional SEM observation of Mo-Ti-Ag layered composite material
[0131] The test method is the same as that in Test Example 1, and the test results are similar to those in Test Example 1. Layer 1 is an Ag film with a thickness of 5 microns; Layer 2 is a Ti intermediate layer with a thickness of about (0.5) microns; and Layer 3 is a Mo foil. The interface bonding between Ag / Ti and Ti / Mo is average). In addition, the Ag film has a columnar crystal characteristic crystal particle structure. At the interface between Ag / Ti and Ti / Mo, it is shown that a metallurgical bond is formed at the interface.
[0132] 9) Interface bonding strength test of Mo-Ti-Ag layered composite materials
[0133] The test method was the same as that in Test Example 1. The test results showed that the maximum load was 2175 N and the tensile strength was 31 MPa.
[0134] in conclusion
[0135] The tensile strengths of Test Examples 1, 2, and 3 are similar to that of Comparative Example 1. However, the preparation of the Mo-Ti-Ag layered composite material in Comparative Example 1 requires a relatively high purity of the material, and the cost is also relatively high.
[0136] The metal interfaces of Test Examples 1, 2, and 3 formed a metallurgical bonding interface with better bonding strength than those of Comparative Examples 2 and 3, and did not crack due to temperature differences and different expansion coefficients. The tensile strength was much higher than that of the comparative examples.
[0137] The preparation method of the present invention prepares the silver film layer by a multifunctional vacuum coating machine, and under vacuum conditions, assisted by ion source technology, through two high-temperature annealings, successfully prepares a silver / metal intermediate layer / molybdenum layered composite material on the molybdenum surface. The method is environmentally friendly, has high process stability, and can be mass-produced, and solves the problems of the current molybdenum foil surface electroplating silver process having a non-dense coating layer and poor interface bonding.
[0138] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a silver film layer on the surface of a molybdenum foil, characterized in that: 1) placing the pretreated molybdenum foil substrate under vacuum conditions and performing ion source bombardment cleaning; 2) Titanium coating: The molybdenum foil substrate is heated at high temperature under vacuum conditions, and a titanium coating is first deposited using an electron gun, and an ion source is turned on to assist in the titanium coating. + Bombard the titanium film layer, rotate the molybdenum foil substrate, evaporate the titanium film layer on the first side of the molybdenum foil substrate, and stop when the thickness of the titanium film layer is reached. After the evaporation of the first titanium film layer is completed, then evaporate the titanium film layer on the second side of the molybdenum foil substrate. The process is the same as that of evaporating the first titanium film layer. After the evaporation is completed, turn off the ion source and perform the first annealing treatment; 3) Silver-plated film layer: The process of evaporating the silver film layer is the same as that of evaporating the titanium film layer in step 2). After the evaporation is completed, the ion source is turned off and a second annealing treatment is performed; 4) Packaging: The molybdenum foil after step 3) is cooled to room temperature and packaged with nitrogen.
2. The method according to claim 1, characterized in that: The thickness of the titanium-plated film layer in step 2) is 15 nm to 600 nm, preferably 100 nm to 600 nm.
3. The method according to claim 1, characterized in that: In step 2), the molybdenum foil substrate is heated to a temperature of 300-500°C.
4. The method according to claim 1, characterized in that: In step 2), the electron gun power parameters are adjusted to: high voltage: 6-10KW, beam current: 0.05-0.3A, filament voltage: 50-70V, filament current: 1-2A, evaporation rate: 1.5-3nm / s.
5. The method according to claim 1, characterized in that: In step 2), the ion source parameters are adjusted to: acceleration current of 5-15 mA, ion beam current of 80-100 mA, plate voltage of 340-360 V, anode current of 2-5 A, cathode filament current of 14-17 A.
6. The method according to claim 1, characterized in that: The evaporated silver film layer has an evaporation thickness of 3 to 7 μm.
7. The method according to claim 1, characterized in that: The evaporation time of the silver film layer is 20 to 50 minutes.
8. The method according to claim 1, characterized in that: After the first titanium film layer is evaporated in step 2), the molybdenum foil substrate is turned 180 degrees to the back side, and then the second titanium film layer is evaporated on the molybdenum foil substrate.
9. The method according to claim 1, characterized in that: The temperature of the first annealing is 700-900°C, and the temperature of the second annealing is 650-900°C.
10. The method according to claim 1, characterized in that: The time of the first annealing and the second annealing is 10 to 30 minutes.
Citation Information
Patent Citations
Surface treatment process of molybdenum foil for spaceflight interconnection piece
CN106048534A